Ben Bende Değilim - Mehmet Tayfun Gülle (Türk Kütüphaneciliği)
The book includes memoirs of Mr. Yildirim who was author of the mentioned book also retired librarian. Author with beard and liken to different characters by people all the time so he shared his memoirs with dry humour.